Phonetic convergence in the shadowing for natural and synthesized speech in Polish - Jankowska, Karolina; Kuczmarski, Tomasz; Demenko, Grażyna (Lingua Posnaniensis, 2020)
The matter of shadowing natural speech has been discussed in many studies and papers. However, there is very little knowledge of human phonetical convergence to synthesized speech. To find out more about this issue an experiment in the Polish language was conducted. Two types of stimuli were used – natural speech and synthesised speech. Five sets of sentences with various phonetic phenomena in Polish were prepared. A group of twenty persons were recorded which gave the total number of 100 samples for each phenomenon. The summary of results shows convergence in both natural and synthesised speech in set number 1, 2, 4 while in group 3 and 5 the convergence was not observed. The baseline production shown that the great majority of participants prefer ɛn/ɛm version of phonetic feature which was reflected in 83 out of 100 sentences. In the shadowing natural speech participants changed ɛn/ɛm to ɛw/ɛ̃ in 26 cases and in 4 ɛw/ɛ̃ to ɛn/ɛm. When shadowing synthesised speech shift from ɛn/ɛm to ɛw/ɛ̃ in 18 sentences and 4 from ɛw/ɛ̃ to ɛn/ɛm. The intonation convergence was also observed in the perceptual analysis, however the analysis of F0 statistics did not show statistically significant differences.